Customer service : a practical approach - Harris, Elaine K. (Upper Saddle River, N.J. : Prentice Hall, 2000)
What is Customer Services? The Challenges of Customer Service. Strategy and Formulating a plan for Success. Communications in Customer Service. Coping with Challenging Customers...
Keywords: Customer services; Customer services